Image analysis of oxidative and glycolytic muscle fibers during reperfusion injury by segmentation based on regions (2016)
Different situations cause ischemia and reperfusion injury, affecting tissues under the level of compression. In this research, abnormal characteristics in distribution of muscle fibers types in soleus and extensor carpi radialis longus, during short periods of ischemia and short and long periods of reperfusion, were determined. Fibers were classified by enzyme histochemistry techniques NADH-TR and myosin-ATPase. Measurements of areas were carried out through semiautomatic image processing by using segmentation based on regions, which evidenced significant changes in distribution during reperfusion followed to one and three hours of ischemia, as well as in comparisons of areas for all periods of reperfusion. This study strengthens the evidence about using practical procedures of image analysis in the diagnosis of tisular abnormalities.